Penguins at home : gentoos of Antarctica - McMillan, Bruce (Boston : Houghton Mifflin, 1993)
Describes the physical characteristics, behavior, and life cycle of the timid gentoo penguin.
Includes bibliographical references (p. 32) and index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
Booklist, October 2008.
Bulletin (Center for Children's books), January 1999.
Keywords: Gentoo penguin -- Antarctica -- Juvenile literature; Gentoo penguin; Penguins; Gentoo penguins; Penguins